2020
DOI: 10.2478/raon-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of (1→3)-β-D-glucan to predict Pneumocystis jirovecii pneumonia in non-HIV-infected patients

Abstract: BackgroundPneumocystis jirovecii pneumonia (PCP) is a common and potentially fatal opportunistic infection in immunocompromised non-HIV individuals. There are problems with clinical and diagnostic protocols for PCP that lack sensitivity and specificity. We designed a retrospective study to compared several methods that were used in diagnostics of PCP.Patients and methodsOne hundred and eight immunocompromised individuals with typical clinical picture for PCP and suspicious radiological findings were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
6
0
3
Order By: Relevance
“…The role of the BDG assay in the diagnosis of PcP has been intensely discussed: its major asset is its high negative predictive value, but its high sensitivity and lack of specificity due to factors that interfere with the tests [ 66 , 74 , 75 , 76 , 77 ] can lead to false-positive results. Based on this, it was recommended as a screening test and that higher cutoff values should be used for the diagnosis of PcP, up to 400 pg/mL in AIDS or non-HIV infected patients [ 57 , 78 , 79 ]. Indeed, in our study, the group of patients having PcP presented mean BDG values of 441 pg/mL ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the BDG assay in the diagnosis of PcP has been intensely discussed: its major asset is its high negative predictive value, but its high sensitivity and lack of specificity due to factors that interfere with the tests [ 66 , 74 , 75 , 76 , 77 ] can lead to false-positive results. Based on this, it was recommended as a screening test and that higher cutoff values should be used for the diagnosis of PcP, up to 400 pg/mL in AIDS or non-HIV infected patients [ 57 , 78 , 79 ]. Indeed, in our study, the group of patients having PcP presented mean BDG values of 441 pg/mL ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…[7] We determined sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of BDG (above or below 80 and 400 pg/mL (five-times diagnostic threshold) for diagnosis of PCP. [8]…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it was suggested that a negative BG result could accurately exclude a PCP diagnosis (Held et al, 2011;Onishi et al, 2012;Alanio et al, 2016;Lahmer et al, 2017;Morjaria et al, 2019;Ideguchi et al, 2020;Szvalb et al, 2020). In contrast, other reports describe a suboptimal sensitivity of this assay, especially in HIV-negative patients (Nakamura et al, 2009;Li et al, 2015;Engsbro et al, 2019;Kato et al, 2019;Del Corpo et al, 2020;Mercier et al, 2020;Rogina and Skvarc, 2020). These discrepant results regarding the usefulness of serum BG assay in HIV-negative PCP patients could be related to the underlying condition that exposes to PCP risk.…”
Section: Introductionmentioning
confidence: 99%